Uma abordagem para a personalização automática de interfaces de usuário para dispositivos móveis em ambientes pervasivos - Martini, Ricardo Giuliani (2012)
The great advance in the semiconductor industry allowed a increase in the development and marketing of mobile electronic devices. With the expansion of this market, the need for new programming methods and a different view for the development of user interfaces increased. Interfaces that were used before only in desktops and relied on keyboard and mouse interaction are now used in a variety of devices, including cell phones, smartphones and tablets. Often making the use of touch screens as well as by voice commands. Taking into account these aspects of cross-platform and different usability, it becomes apparent the importance of interfaces that adapt "to the environment." With the advent of mobile devices, this particular area became of fundamental importance because this kind of devices has specifics characteristics that are essential to the composition of a satisfactory user interface. So, mobile devices are covering a large variety of features, which makes the interfaces development a very complex task. One way to develop and adapt user interfaces in order to facilitate handling and to reduce stress at the time of use of the device is through the use of user profiles and capabilities of devices. Therefore, that interface is adapted to the user needs and preferences, as well be able to fully adapt to the device features. Considering this assumption, this dissertation aims to present the architecture PIDIM. This architecture goal to assist in the customization and adaptation of user interfaces for mobile devices in pervasive environments. The user interfaces adapted for this process plans to facilitate the use of mobile devices. The proposed approach presents an architecture that uses concepts of Pervasive Computing enabling information access anytime, anyplace, and in any computing device. Besides, it represents data on the user s profile, so that adaptation of the interfaces is entirely focused on the end user. The knowledge representation about the user profile needed for PIDIM architecture modeling is done through ontologies due to the possibility of reuse of stored information. In order to validate and demonstrate the flow of operation of the proposed approach is presented a case study in the literature, which has as scenario the adaptation of user interfaces when it is in motion.